Learning and individual differences in skilled competency‐based performance: Using a course planning and learning tool as an indicator for student success. Issue 3 (13th September 2021) - Gyll, Sean P.; Hayes, Heather
Abstract: Competency‐based institutions eager to improve student outcomes would be wise to consider research‐based measures, such as a course planning and learning tool (CPLT), as one step in the student life cycle. Recent research has indicated which assessment practices tend to be most successful in an online competency‐based environment while hinting at which specific study characteristics are likely to lead to superior performance. Our objective was to develop a more successful and scientifically measurable process than any other method that currently exists by reducing the gap between the uncertainty and subjective randomness that currently detracts from educating students and increasing institutions' ability to engage with students in a meaningful manner. We investigated students' prior Knowledge, Confidence level in completing the course, and Experience with course content, and their relationship to the use of online Learning Resources, frequency of Formative Assessment Practice, Formative Assessment Performance, frequency of Course Mentor interactions, and Course Pace. Results showed that students' Knowledge, Confidence, and Experience have notably different impacts on study behavior and performance outcomes. Specifically, students with higher Knowledge perform well despite less studying, students with higher Confidence also perform well, but students with high Experience struggle more with the course material and performance. Implications for academic planning in an asynchronous environment are discussed.